2011
DOI: 10.3844/ajassp.2011.277.283
|View full text |Cite
|
Sign up to set email alerts
|

IPACT: Improved Web Page Recommendation System Using Profile Aggregation Based On Clustering of Transactions

Abstract: Problem statement: Recently, Web usage mining techniques have been widely used to build recommendation systems especially for anonymous users. Approach: Assigning the current user to the best web navigation profile with similar navigation activities will improve the ability of the prediction engine to produce a recommendation list then introduce it to the user. This study presents iPACT an improved recommendation system using Profile Aggregation based on Clustering of Transactions (PACT). Results: iPACT shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…5) show the average precision and recalling for the suggestions presented to several users using the proposed method. These figures show the result of the comparison between proposed method despite using date in user profile and the proposed method (without inclusion of date), the IPACT system proposed in (AlMurtadha et al, 2011) and user natural behavior. …”
Section: Assessment Of the Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5) show the average precision and recalling for the suggestions presented to several users using the proposed method. These figures show the result of the comparison between proposed method despite using date in user profile and the proposed method (without inclusion of date), the IPACT system proposed in (AlMurtadha et al, 2011) and user natural behavior. …”
Section: Assessment Of the Proposed Methodsmentioning
confidence: 99%
“…Afterwards, suggestions were provided to users through user review records and the extracted knowledge. Almurtadha et al (2011) introduced a recommender system to explore user priorities and suggested pages for future reviews. This system includes two phases.…”
Section: Related Workmentioning
confidence: 99%
“…This is so due to the following characteristics of the Web: (1) the amount of data/information on the Web is huge and still growing rapidly. (AlMurtadha et al, 2011;Al Shalabi, 2009)Web data is also easily accessible, (2) the coverage of Web information is wide and diverse. One can find information about almost anything on the Web, (3) Information on the Web is heterogeneous, (4) Much of the Web information is semi-structured due to the nested structure of HTML code and the need of Web page designers to present information in a simple and regular fashion to facilitate human viewing and browsing, (5) Much of the Web information is linked.…”
Section: Introductionmentioning
confidence: 99%
“…User interest may change over time so that profiles are maintained and updated. An improved recommendation system using Profile Aggregation based on Clustering of Transactions (iPACT) shows better prediction accuracy than the previous methods PACT and Hypergraph (Almurtadha et al, 2011). To maintain the interest scores of the user profile, spreading activation algorithm is proposed to analyse ongoing browsing activities (Sieg et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%